Flight-Fecundity Trade-offs: A Possible Mechanistic Link in Plant–Herbivore–Pollinator Systems - Davidowitz, Goggy; Bronstein, Judith L.; Tigreros, Natasha (Frontiers in Plant Science, 2022)
Plant-herbivore and plant-pollinator interactions are both well-studied, but largely independent of each other. It has become increasingly recognized, however, that pollination and herbivory interact extensively, with consequences for plant fitness. Here, we explore the idea that tradeoffs in investment in insect flight and reproduction may mechanistically link pollination and herbivory. We focus here on Lepidoptera: larvae are generally herbivores while most adults are pollinators, making them ideal to study these links. Increased allocation of resources to flight, we argue, potentially increases an insect pollinator’s efficiency, resulting in higher plant fitness. In contrast, allocation of resources to reproduction in the same insect species reduces plant fitness, because it leads to an increase in herbivore population size. We first provide a general background on tradeoffs between flight and fecundity in insects. We then examine the sequence of resource pools available to herbivorous Lepidopteran larvae (maternally provided nutrients to the eggs, as well as leaf tissue), and to adults (nectar, and nuptial gifts provided by the males to the females), which potentially are pollinators. Last, we discuss how subsequent acquisition and allocation of resources from these pools may alter flight-fecundity tradeoffs, with concomitant effects both on pollinator performance and the performance of larval herbivores in the next generation. Allocation decisions at different times during ontogeny translate into costs of herbivory and/or benefits of pollination for plants, mechanistically linking herbivory and pollination.